Painting, Literature and Film in Colombian Feminine Culture, 1940-2005: Of Border Guards, Nomads and Women - Martin, Deborah (Cambridge University Press, 2013)
This book explores crucial moments in the emergence of feminine culture in Colombia hitherto unexamined in English-language criticism through an examination of the work of ground-breaking artist Débora Arango, best-selling novelist Laura Restrepo, and three generations of documentary filmmakers.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Spirale, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Section: 89 pages : illustrations en couleur ; 26 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

WàCOLETIVO : Broderie, couture et crochet comme art contemporain dans l'espace public - WàCOLETIVO (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Visionarias de la perspectiva de género en el arte contemporáneo del Caribe colombiano - Flórez, Alexa Cuesta (Memoria y Sociedad, 2017)
La perspectiva de género en el arte del Caribe colombiano se puede contextualizar con el movimiento feminista planetario. La comparación se establece en las creaciones de mujeres artistas de esta región, ya que subvierten, manifiestan y revelan con denotada libertad expresiva, no solamente sus inquietudes intimistas, sino toda una serie de cuestionamientos a las condiciones que culturalmente se le han impuesto a la mujer en el Caribe. Son dos generaciones diferentes; las primeras, analizadas en esta entrega, pueden ser catalogadas como pioneras de la perspectiva de género en el arte colombiano. Las segundas, consolidan problemáticas en apuestas individuales, de manera diaspórica y cada vez más comprometidas con el movimiento social de mujeres. En ambos casos lo hacen a través de las artes visuales, audiovisuales, performáticas e híbridas. Estamos ante artistas vanguardistas, de las artes visuales y performáticas en el Caribe colombiano; preferimos llamarlas, en ambos casos, visionarias. Gender perspective in the Colombian Caribbean art can be contextualized within the worldwide feminist movement. The comparison is established in the artwork of female artists from this region, as they subvert, demonstrate, and reveal with poignant expressive freedom, not only their intimate concerns, but a whole series of questions to the conditions that have been culturally imposed on women in the Caribbean. They come from two different generations. The first generation, analyzed in this installment, can be defined as the pioneers of gender perspective in Colombian art. The second generation consolidates issues through individual pledges in a diasporic way and increasingly committed to the social women’s movement. Both generations do this through performative, hybrid, visual and audiovisual art. These are avant-garde artists of the visual and performative art in the Colombian Caribbean. We prefer to call them, in both cases, visionaries.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Related with the book "Eros ideologies. Writings on art, spirituality, and the decolonial" of Laura Pérez
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Related with the Podcast "Interview with author, Dr. Laura Pérez"
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Revista N'oj : Issue No.2 (2020) Event was sponsored by the Latinx Research Center at the University of California, Berkeley
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé